133k views
15 votes
What will be the result of substituting 2 for x in both expressions below?

One-half x + 4

x + 6 minus one-half x minus 2
Both expressions equal 5 when substituting 2 for x because the expressions are equivalent.
Both expressions equal 6 when substituting 2 for x because the expressions are equivalent.
One expression equals 5 when substituting 2 for x, and the other equals 2 because the expressions are not equivalent.
One expression equals 6 when substituting 2 for x, and the other equals 2 because the expressions are not equivalent.

User Cherrun
by
5.2k points

2 Answers

9 votes

Answer:

A

Explanation:

User Imhotap
by
5.9k points
11 votes
It’s the first answer, both expressions equal 5 when substituting 2 for x because the expressions are equivalent.

1/2 of x +4
=1/2(2)=1.
1+4= 5

2+6=8
1/2(2)=1.
8-1=7
7-2=5
User Tanwer
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.